Effect of establishment methods & 4HPPD inhibitors on weeds, productivity and economicsof Kharif maize under Bael based agri-horti system - Sanodiya, Pratik; Sonowal, Tridib (Indian Journal of Agroforestry, 2025)
The application of optimal establishment methods and proper weed control measures is of great significance to controlling weeds in a field and boosting productivity of crops. This study was conducted at Agricultural Research Farm, Rajiv Gandhi South Campus, Banaras Hindu University, Barkachha, Mirzapur, Uttar Pradesh, during kharif season of 2022 to study the effect of different establishment methods and herbicidal treatments on weeds, crop growth, yield and economics of maize and bael under the agri-horti system of plantation. The experiment was conducted in a randomized complete block design with two factors, establishment methods and herbicidal treatments. The ridge and furrow method of establishment was efficient in controlling weeds and improved maize productivity over the use of conventional method of establishment. Also, the application of atrazine 1.0 kg/ha PE fb topramezone 25.2 g/ha at 25 DAS for weed control was found to be superior over other herbicidal treatments. The treatment atrazine 1.0 kg/ha PE fb topramezone 25.2 g/ha at 25 DAS recorded significantly higher grain yield and stover yield 48.42 q/ha and 58.33 q/ha as compared to the other herbicidal treatment of atrazine 1.0 kg/ha PE fb halosulfuron 67.5 g/ha at 25 DAS of 37.65 q/ha and 46.56 q/ha, respectively. Consequently, the application of ridge and furrow establishment method along with atrazine 1.0 kg/ha PE fb topramezone 25.2 g/ha at 25 DAS as a weed control measure was observed to bring in significantly superior combined economics of maize along with bael in the system with a B:C ratio of 3.49.